Identification, Characterization, and Expression Profile Analysis of the mTERF Gene Family and Its Role in the Response to Abiotic Stress in Barley (Hordeum vulgare L.) - Li, Tingting; Pan, Wenqiu; Yuan, Yiyuan; Liu, Ying; Li, Yihan; Wu, Xiaoyu; Wang, Fei; Cui, Licao (Frontiers in Plant Science, 2021)
Plant mitochondrial transcription termination factor (mTERF) family regulates organellar gene expression (OGE) and is functionally characterized in diverse species. However, limited data are available about its functions in the agriculturally important cereal barley (Hordeum vulgare L.). In this study, we identified 60 mTERFs in the barley genome (HvmTERFs) through a comprehensive search against the most updated barley reference genome, Morex V2. Then, phylogenetic analysis categorized these genes into nine subfamilies, with approximately half of the HvmTERFs belonging to subfamily IX. Members within the same subfamily generally possessed conserved motif composition and exon-intron structure. Both segmental and tandem duplication contributed to the expansion of HvmTERFs, and the duplicated gene pairs were subjected to strong purifying selection. Expression analysis suggested that many HvmTERFs may play important roles in barley development (e.g., seedlings, leaves, and developing inflorescences) and abiotic stresses (e.g., cold, salt, and metal ion), and HvmTERF21 and HvmTERF23 were significant induced by various abiotic stresses and/or phytohormone treatment. Finally, the nucleotide diversity was decreased by only 4.5% for HvmTERFs during the process of barley domestication. Collectively, this is the first report to characterize HvmTERFs, which will not only provide important insights into further evolutionary studies but also contribute to a better understanding of the potential functions of HvmTERFs and ultimately will be useful in future gene functional studies.